1981
DOI: 10.1111/j.1600-0773.1981.tb01631.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Manganese on Synthesis of Brain Catecholamines in Growing Rats

Abstract: The effect of short‐term exposure of manganese on the synthesis of brain catecholamines in growing rats has been investigated by using two methods, 1) measuring the amount of conversion of 3,5‐3H‐tyrosine to 3H‐labelled dopamine and norepinephrine, and 2) measuring the rate of decline of endogenous dopamine and norepinephrine following inhibition of their synthesis with α‐methyl‐p‐tyrosine. The magnitude of conversion of 3,5‐3H‐tyrosine to 3H‐dopamine and 3H‐norepinephrine in the brain at 60 min after the admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…However, there is no information concerning the effects of Mn on the muscle physic properties, antioxidant and the Nrf2 and TOR signaling in animals. In growing rat brain, Mn could influence the synthesis of catecholamine (Chandra & Shukla, 1981). It was reported that one of the catecholamine, epinephrine, could regulate the Nrf2 activity in rat astrocyte (Shih, Erb, & Murphy, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no information concerning the effects of Mn on the muscle physic properties, antioxidant and the Nrf2 and TOR signaling in animals. In growing rat brain, Mn could influence the synthesis of catecholamine (Chandra & Shukla, 1981). It was reported that one of the catecholamine, epinephrine, could regulate the Nrf2 activity in rat astrocyte (Shih, Erb, & Murphy, 2007).…”
Section: Introductionmentioning
confidence: 99%